Occurrence State of Carbon and Electrolyte in Anode Carbon Residue From Electrolytic Aluminum - Mao, Song; Zhang, Qin (Frontiers in Materials, 2021)
Anode carbon residue is produced in the production of electrolytic aluminum. Its properties need to be studied for secondary utilization. In this paper, mineralogy of anode carbon slag from an electrolytic aluminum plant in Guizhou was studied , the anode residue chemical composition, structure, mineral composition, occurrence state of main elements, etc, was investigated, the results show that: Anode carbon residue is mainly composed of 14 minerals such as cryolite, cryolithionite, elpasolite and graphite. Among them, the opaque minerals are mainly graphite and the transparent minerals are mainly cryolite. Carbon in the form of independent mineral occurrence in graphite, fluoride in the form of independent mineral occurrence in cryolite, cryolithionite, elpasolite and fluorite, aluminum in the form of independent mineral occurrence in cryolite, cryolithionite, elpasolite, aluminium oxide and magnesium aluminate, sodium in the form of independent mineral occurrence in cryolite, cryolithionite, elpasolite. The mineralogical characteristics and occurrence state of carbon and electrolyte were studied, which provided a basis for the separation and recovery of carbon and electrolyte in anode carbon residue.